PELAKSANAAN PEMENUHAN HAK KORBAN PELANGGARAN HAK ASASI MANUSIA GENOSIDA BERDASARKAN UNDANG-UNDANG NO.26 TAHUN 2000 - Widayati, Kunti (Universitas 17 Agustus 1945 Samarinda, 2017)
Serious violations of human rights Genocide is an extraordinary crime that results in material and immaterial losses. The Victims who have experienced crime Genocide often do not get the protection and fulfillment as to the rights owned in accordance with the provisions of applicable legislation under Law No. 26 of 2000 with Government Regulation No. 2 and No. 3 of 2002. Â Based on the results of the research, it can be seen that victims of human rights violations Genocide has the right to get protection, commensation, restitution, and rehabilitation. Various Efforts that can be carried out by the government to address the fulfillment of the rights of the victims / heirs In this case the role of the Government in fulfilling the implementation of human rights, both in respect, protection and promotion of human rights and the responsibility of the Government to perform the rights and obligations related to pay compensation against the victim. Principally The process of resolving human rights violations of Genocide by means of / stage through Komnas HAM, Human Rights Court, Truth and Reconciliation Commission and Ad Hoc Human Rights Court. While the fulfillment of the rights of victims in the form of compensation as well as: Compensation, Restitution, and Rehabilitation and provide protection for victims and witnesses.